Efeitos da atividade fÃsica sobre os nÃveis de colesterol total, glicose e triglicerÃdeos: uma avaliaÃÃo econÃmica do Programa Eu sou Ativo - Paulo Henrique Sales Nunes (2013)
In this dissertation, itÂs my purpose to evaluate the âEu sou ativoâ programme whose preferable public is mainly compound of Internal Revenue Service civil servants and collaborators at the age of 40 and more. These must be in active part or retired. The programme is of preventive interest by focussing on physical activity guided by a physical education instructor. The programmeÂs beneficiaries can take nutritional/psychological guidance, and other activities like physiotherapy. That said, we estimate, with respect the 2009-2011 period, the members physical activities and their effects, especially on their level of cholesterol, triglycerides and glucose. Our model is the difference in difference. As far as we are concerned with, a few results on the participants connection show that their level of cholesterol (27,73) is not so high after they began the present activity. ThatÂs, the programme is more than helpful for them, meaning that their possibly heart disease is completely reduced. Furthermore, we estimate the economic gains issued from the programme, bearing in mind the âVPLâ whose value is R$ 605.551,70 and the âTIRâ whose tax is 10,71%. As consequence, we can surely state that the programme advantages are beyond the disadvantages, and so its economic evaluation is more than positive.